Arbitration as a dispute resolution tool in the construction industry in Malaysia with specific reference to the Kuala Lumpur regional centre for arbitration / Muhammad Hisham Muhammad Said…[et al.] - Muhammad Said, Muhammad Hisham; Syed Nawawi, Syed Mohamad Ismail (Faculty of Law, 2007)
In this paper, ARBITRATION AS A DISPUTE RESOLUTION TOOL IN THE CONSTRUCTION INDUSTRY IN MALAYSIA WITH SPECIFIC REFERENCE TO KUALA LUMPUR REGIONAL CENTRE FOR ARBITRATION is dealt with The objectives of the paper are four folds; firstly to give a general overview of the construction industry in Malaysia and it commonly associated disputes; secondly to briefly states the dispute resolution methods available for the construction industry in Malaysia; thirdly to give a literature review as well as method and procedure of the Arbitration as a tool for dispute resolution particularly for the construction industry in Malaysia; and finally to conclude on the application and effectiveness of the Arbitration as dispute resolution tools in the construction industry in Malaysia. Emphasis is given on Arbitration Act 2005 (Act 646) as well as ethic and code as practiced by the Kuala Lumpur Regional Centre for Arbitration.